Dalton and Putnam: Teaching Political Polarization to Generation Z Students. Issue 4 (14th October 2021) - McBeth, Mark K.; Belyea, Jules; Perry, Andrew
ABSTRACT: Political polarization and generational politics are important topics in contemporary political science classrooms. This article presents an approach to teaching political polarization in an introduction to politics course. Coauthored by two Generation Z students from the course and their Boomer Generation professor, the article provides conflicting views of young people and politics as found in the work of Robert Putnam and Russell Dalton. The article presents survey data on affective and issue political polarization from the course, including discussion by the two student coauthors of the survey results interpreting their generation's political polarization. The course approaches the introductory politics course using cognitive psychology concepts including confirmative bias, motivated reasoning, and other cognitive biases. Teaching from this micro-level perspective helps students to reflect on their own political biases. The article provides concepts and readings for political science professors to use in replicating the course.